ALLIANCES AND RIVALRIES THE ARABIC QURAYSH TRIBES: INHIBITING FACTOR OF ISLAMIC DA - Pamungkas, Jati (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
The period of Islamic growth in Mecca from 610 to 622 AD can becategorized into a full challenges and full obstacles period. The Islamic da